Incidence and risk factors of hardware-related complications after proximal femoral osteotomy in children and adolescents - Chung, Myung Ki; Kwon, Soon Sun; Cho, Byung Chae; Lee, Gye Wang; Kim, Jaeyoung; Moon, Seung Jun; Lee, Jae Woo; Chung, Chin Youb; Sung, Ki Hyuk; Lee, Kyoung Min; Park, Moon Seok (Journal of Pediatric Orthopaedics Part B, 2018)
Proximal femoral osteotomy has been used in cerebral palsy, Perthes disease, hip dysplasia, idiopathic femoral anteversion, and various hip diseases in children and adolescents. Conventionally, a blade plate (BP) has been used. However, the pediatric locking compression plate (LCP) has recently been applied widely. We compared the hardware-related complications of the BP and the LCP as well as the factors influencing these complications in patients who have undergone a proximal femoral osteotomy in children and adolescents. We enrolled consecutive patients aged less than or equal to 20 years who had undergone proximal femoral osteotomy with BP or LCP between May 2003 and December 2014, and who were followed up until 6 months after hardware removal. Following consensus building, hardware-related complications were identified from the patients' medical records and hip radiographs. Patient age, sex, type of plate, and Gross Motor Function Classification System (GMFCS) level in cerebral palsy patients were evaluated as possible risk factors, and a generalized estimating equation was used to assess the risk factors for hardware-related complications. A total of 417 hips from 251 patients were finally included in this study. Seven losses of fixation around the plate (five patients, 3.0%) occurred in the BP, three implant-related fractures (three patients, 3.6%) occurred in the LCP, and there was no significant difference (P=0.74). All hardware-related complications occurred in cerebral palsy patients, and the implant-related fractures occurred in patients with GMFCS IV/V. The risk of complications increased with age (P=0.002). The risk of loss of fixation around the BP is a well-known complication. However, LCP is not without hardware-related complications. The LCP provides strong stability of fixation. However, it is speculated that the LCP is related to implant-related fractures because of the stress shielding effect. Therefore, care should be exercised when using a locking plate in patients with osteoporosis, such as cerebral palsy with GMFCS IV/V. Level of Evidence: Therapeutic Level III.
Keywords: Adolescent; Bone Plates; Child; Child, Preschool; Female; Humans; Incidence; Male; Osteotomy; Postoperative Complications; Prosthesis Failure; Retrospective Studies; Risk Factors; Young Adult; blade plate; cerebral palsy; femoral osteotomy; hardware-related complications; locking hip plate